Approaches for Recognition of Public-Private Partnership Assets – Accounting Issues - Markova, Maria (Research Papers, 2020)
The concept of control is increasingly emerging as a basis for the recognition of assets and revenues. The author has attempted to analyze the impact of the implementation of this concept on the recognition of PPP assets.  The author comes to the conclusion that the classification of a lease or concession service is based on an in-depth analysis of a set of clauses in the PPP contract that classify the infrastructure either as a lease asset (IFRS16), or an intangible, respectively financial asset, in accordance with IFRIC Interpretation 12.
Keywords: Public-private partnership; Lease; Concessions; Concept of control; Accounting